BVS restenosis: "Reappearance of the disappeared stent". Issue 2 (19th September 2018) - Seth, Ashok; Kumar, Dhananjay
Key Points: This article describes for the first time the pattern of restenosis within Bioresorbable Vascular Scaffold and its predictors. The focal in -BVS restenosis can usually be treated with repeat percutaneous coronary intervention. Longer term follow up beyond one year in a larger cohort is needed to define the impact of restenosis pattern on clinical outcomes.